2014
DOI: 10.1039/c3dt52406j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural characterization of 14-vertex germa-, stanna-, and plumba-carboranes

Abstract: This article reports the synthesis and structures of several 14-vertex germa-, stanna-, and plumba-carboranes of the MC2B11 system. The reaction of GeCl2·dioxane, SnCl2 or Pb(OAc)2 with [8,9-(CH2)3-8,9-C2B11H11][Na2] in THF gave, after recrystallization from bidentate ligands such as bipyridine, 4,4'-dimethyl-2,2'-bipyridine, phenantroline and 1,2-bis(diphenylphosphino)ethane (dppe), eight 14-vertex p-block metallacarboranes 2,3-(CH2)3-1-(2',2''-bipyridine)-1,2,3-GeC2B11H11 (1), 2,3-(CH2)3-1-(4',4''-dimethyl-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Instead, it affords a structural isomer of CAd 14-vertex closo -carborane. On the other hand, both 13- and 14-vertex nido -carborane dianions are a class of useful synthons for the preparation of 14- and 15-vertex metallacarboranes via polyhedral expansion methodology. Thus, 14-vertex closo -carboranes and 15-vertex metallacarboranes represent the largest carboranes and metallacarboranes known so far.…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…Instead, it affords a structural isomer of CAd 14-vertex closo -carborane. On the other hand, both 13- and 14-vertex nido -carborane dianions are a class of useful synthons for the preparation of 14- and 15-vertex metallacarboranes via polyhedral expansion methodology. Thus, 14-vertex closo -carboranes and 15-vertex metallacarboranes represent the largest carboranes and metallacarboranes known so far.…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…The chemical shifts of the unique B atoms bound to NHCs fell in the range −1.4-−3.8 ppm with J BH = 40-84 Hz, suggesting that this boron still binds to an exo-hydrogen atom. In addition, the proton coupled 11 B NMR spectra showed one singlet at 13.9 ppm in 5, 13.5 ppm in 6, 13.2 ppm in 7, 13.6 ppm in 8, 13.0 ppm in 11, and 11.5 ppm in 12 corresponding to the BPh vertex in these complexes.…”
Section: Synthesismentioning
confidence: 87%
“…We wondered whether such a salt is an intermediate for the formation of the final products 1-12. To this end, 11 9 it is suggested that the deprotonation of α-methylene in 13-vertex carboranes proceeds instantly after mixing with NHC to afford the imidazolium salt of carborane anion that is slowly converted to the final product 1.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation